1996
DOI: 10.1002/jlb.60.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional heterologous receptor desensitization between both the fMLP and C5a receptor and the IL-8 receptor

Abstract: During inflammation neutrophils receive multiple signals that are integrated, allowing a single modified response. One mechanism for this discrimination is receptor desensitization, a process whereby ligand-receptor binding is disassociated from cell activation. We examined the effect of heterologous receptor desensitization on neutrophil chemotaxis, calcium mobilization, and arachidonic acid production, using interleukin-8 (IL-8), C5a, and N-formyl-methionyl-leucyl-phenylalanine (fMLP). We observed reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Activation of neutrophils through FPRs induces a variety of pro-inflammatory and antibacterial effector mechanisms including production of ROS, and release of antimicrobial peptides (AMPs) and hydrolytic enzymes from intracellular granules [20]. Furthermore, FPRs regulate the inflammatory reactions in neutrophils by modulating signaling through many other receptors in a process termed receptor cross-talk [21][22][23][24]. The role of FPRs in regulation of inflammation is highlighted by their suggested involvement in both systemic [25] and local [26][27][28] inflammatory responses.…”
Section: Of 52mentioning
confidence: 99%
“…Activation of neutrophils through FPRs induces a variety of pro-inflammatory and antibacterial effector mechanisms including production of ROS, and release of antimicrobial peptides (AMPs) and hydrolytic enzymes from intracellular granules [20]. Furthermore, FPRs regulate the inflammatory reactions in neutrophils by modulating signaling through many other receptors in a process termed receptor cross-talk [21][22][23][24]. The role of FPRs in regulation of inflammation is highlighted by their suggested involvement in both systemic [25] and local [26][27][28] inflammatory responses.…”
Section: Of 52mentioning
confidence: 99%
“…For example, asymmetric heterologous desensitization of certain peptide chemoattractant receptors has been reported [172,173] and we have recently observed that MCP-1 signaling through CCR2b can desensitize subsequent signaling by cognate ligands through the major HIV-1 coreceptors, CCR5 and CXCR4 [85]. Therefore, studies looking at the effect of chemokine secretion on HIV-1 replication or infection may have to be expanded to include non-cognate ligands (like MCP-1), which can potentially affect the expression and/or function of cognate coreceptors.…”
Section: Other Regulators Of Chemokine Effector Functionsmentioning
confidence: 99%
“…Indeed, the stimulation of FPR1 with fMLF desensitized not only FPR1 but also C5aR and chemokine (C-X-C motif) receptor 2 (CXCR2), and inhibited neutrophil responses, such as calcium mobilization and chemotaxis, which are induced by C5a or IL-8. [13][14][15][16][17] It has also been reported that fMLF induces the internalization of CXCR2 from the cell surface as a result of cross-desensitization. 17 C5a and IL-8 can also cross-desensitize FPR1, but there is a hierarchy in the ability to induce cross-desensitization among chemoattractants, with a rank order of fMLF > C5a > IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…tion has previously been demonstrated only under in vitro conditions. Although fMLF-induced cross-desensitization in vitro has been well documented, [13][14][15][16][17] in most cases it has been reported that the administration of fMLF in vivo induces typical effects of chemoattractants on neutrophils, such as neutrophil infiltration into the airway induced by the inhalation of fMLF [22][23][24] and transient neutropenia induced by the intravenous administration of fMLF. 25,26 Among these studies, only Ley et al 25 reported the possibility of an inhibitory effect of fMLF on neutrophil migration towards chemoattractants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation